2015
DOI: 10.2807/1560-7917.es2015.20.19.21125
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical pattern of Francisella tularensis in a nationwide outbreak of tularaemia in Norway, 2011

Abstract: In 2011, a nationwide outbreak of tularaemia occurred in Norway with 180 recorded cases. It was associated with the largest peak in lemming density seen in 40 years. Francisella tularensis was isolated from 18 patients. To study the geographical distribution of F. tularensis genotypes in Norway and correlate genotype with epidemiology and clinical presentation, we performed whole genome sequencing of patient isolates. All 18 genomes from the outbreak carried genetic signatures of F. tularensis subsp. holarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…3B). This corroborates previous findings on the possible long-distance movement of F. tularensis clones (8, 9). In this case, a USSR origin is also supported by historical data on movement of 24 muskrats ( Ondatra zibethica ) from the USSR into the Srebarna reserve in 1956 for the purpose of hunting and production of fur (11).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3B). This corroborates previous findings on the possible long-distance movement of F. tularensis clones (8, 9). In this case, a USSR origin is also supported by historical data on movement of 24 muskrats ( Ondatra zibethica ) from the USSR into the Srebarna reserve in 1956 for the purpose of hunting and production of fur (11).…”
Section: Resultssupporting
confidence: 92%
“…It was not until November 1997 that a new tularemia focus appeared and new F. tularensis strains were isolated in Bulgaria. Recent genomic epidemiological studies of tularemia in Sweden and Norway have revealed strains that are almost 100% identical at the genome level despite being isolated many years apart and/or separated by several hundreds of km (8, 9). In light of these findings, we asked if the clone/clones that caused the recent epidemics in Bulgaria were the same as those that occurred in the early 1960s.…”
mentioning
confidence: 99%
“…Clade B.6 is found in Western Europe and North America, whereas clade B.12 has been isolated mainly in Eastern Europe, and groups together erythromycin-resistant strains (Vogler et al, 2009). In Germany, Switzerland, Sweden, Norway and Finland, both of these major clades have been detected (Karlsson et al, 2013;Müller et al, 2013;Origgi et al, 2014;Afset et al, 2015;Sissonen et al, 2015;Wittwer et al, 2018). Clade B.16 correlates with biovar japonica, isolated in Japan and recently in Turkey (Ulu-Kilic et al, 2013), China (Wang et al, 2014), and Australia (Eden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Human tularemia cases are most often sporadic. However, tularemia outbreaks have been reported in the last two decades in many countries, including Scandinavia, Turkey, and Spain [ 7 , 8 , 9 , 10 ]. The incidence of tularemia in France is evaluated as between 0.08 and 0.25 cases per 10 5 inhabitants, which corresponds to 50 to 150 annual cases declared to Santé Publique France (the French Institute for Disease surveillance) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%